The Impact of the Principal's Leadership on the Role of Teachers in Implementing School Literacy Activities - Nurmiati; Sari, Siti Mayang; Musdiani (Universitas Veteran Bangun Nusantara, 2024)
The Indonesian government has made significant efforts to enhance literacy at the elementary school level as a foundational aspect of students' educational development and to foster a culture of reading and writing from an early age. This research aims to understand literacy activities in elementary schools to impact students' interest and instill character by studying reading, writing, and cultural literacy. Specifically, the research seeks to determine the impact of principals' leadership on teachers' roles in implementing school literacy activities. Using a qualitative approach, the study's results demonstrate that the leadership of school principals in Cluster VI, Kota Bahagia District, South Aceh, significantly influences the implementation of school literacy programs. Principals with positive personalities, adequate knowledge, a strong understanding of the vision and mission, good decision-making abilities, and effective communication skills are able to support and facilitate teachers in literacy implementation. Literacy is crucial for elementary school students as it enables them to read well, write, listen, and understand the diverse cultures of Indonesia, instilling cultural character from an early age.